Effects of Hybrid Filler and Mixing Equipment on the Mechanical and Thermal Properties of NR/EPDM Rubber Blends - Artchomphoo, Jutatip; Saijun, Diew; Booncharoen, Kamonwan; Sungsee, Pasuta; Rattanapan, Suwat (Indonesian Journal of Chemistry, 2024)
This research evaluated the effects of hybrid fillers and mixing equipment on natural rubber (NR) and ethylene propylene diene monomer (EPDM) properties with an 80/20 ratio. Silica (Si), carbon black (C), china clay (CC), and calcium carbonate (Ca) were used as hybrid fillers. Mixing techniques using two-roll mill and an internal mixer were compared. The study focused on cure characteristics, mechanical properties, and thermal stability. The study found that incorporating hybrid fillers significantly improved the curing process. Blends prepared by an internal mixer had more consistent mechanical properties such as modulus, tear strength, and hardness compared to those prepared by two-roll mill. Blends with Si and C (NE-SiC) showed significant enhancements in tensile and tear strength. Although adding multiple fillers did not accelerate curing, it enhanced the modulus, indicating a potential synergistic effect. The internal mixer method resulted in better elongation at break, except for the NE-SiC-CC.Ca blend, which had reduced flexibility. Thermal analysis revealed higher thermal stability for blends with hybrid fillers, decomposing at elevated temperatures with larger residues, particularly in NE-SiC-CC and NE-SiC-CC.Ca blends. These research findings highlight the critical role of filler types and mixing methods in optimizing the performance of NR/EPDM rubber blends.